Pengaruh Financial Literacy dan Income terhadap Personal Financial Management Behavior pada Generasi Millennial Kota Padang - Indriana Rezkia Putri; Abel Tasman (Universitas Negeri Padang, 2019)
AbstractThis research aims to determine the influence of Financial Literacy and Income with PersonalFinancial Management Behavior of Millennial Generation in Padang. The sample in this researchis 120 respondents who already work in padang and the age between 20 until 39 years old. Thisresearch was analyzed with multiple regression analysis using SPSS program version 25 . Theresult of this research are: (1) Financial Literacy has positive influence and give significant effecton Personal Financial Management Behavior of Millennial Generation in Padang (2) Income haspositive influence and give significant effect on Personal Financial Management Behavior ofMillennial Generation in PadangKeywords: Financial Literacy, Income, Personal Financial Management BehaviorPendahuluan